Penggunaan Media Kahoot Terhadap Peningkatan Penguasaan Kosakata Bahasa Jerman - Zamsinar Zamsinar; Misnah Mannahali; Syamsu Rijal (Universitas Negeri Makassar, 2021)
Abstract. This research was a classroom action research which consisted of two cycles and was conducted online. This study was aimed to determine the improvement of German vocabularies mastery of Nine Senior High School Makassar’s Students Grade X MIA by using Kahoot media. The data in this study consisted of two types of data, including qualitative data and quantitative data. Qualitative data was obtained through observation, while quantitative data was obtained through the results of the first and second cycles of vocabularies mastery tests. The data were analyzed using the percentage technique. The results showed that the mastery of German vocabularies’ average score which obtained by the students in the first cycle reached 65% and the second cycle reached 85%. These results indicated that the use of Kahoot media could improve the mastery of German vocabularies of Nine Senior High School Makassar’s Students Grade X MIA